The transititonal strategy of the inclusive democracy project - Fotopoulos, Takis, (Universidad Nacional de Quilmes, 2004)
Starting point is that the world, at the beginning of the new millennium, faces a multi-dimensional crisis (economic, ecological, social, cultural and political) which is caused by the concentration of power in the hands of various elites, as a result of the establishment, in the last couple of centuries, of the system of market economy, representative democracy and the related forms of hierarchical structure. If we accept this premise, then the obvious way out of this crisis is the abolition of power structures and relations, i.e. the creation of conditions of equal distribution of power among citizens. One way that could bring about this sort of society is strategy proposed by the Inclusive Democracy project, which involves the creation of political, economic and social structures that secure direct democracy, economic democracy, ecological democracy and democracy in the social realm. It also involves the creation of a new social paradigm, which, for the reproduction of inclusive democracy to be secured, has to become dominant.